Effect of Neck and Upper Trunk Exercises in the Management of Mechanical Low Back Pain - Swetha, Sudhakar; Prathap, Suganthirababu; Vinodhkumar, Ramalingam; Vignesh, Srinivasan; Kumaresan, Abathsagayam; Jagatheesan, Alagesan (INTI International University, 2023)
Background: Mechanical low back pain is caused by the overuse of an anatomical or Functional structure (muscle strain), as well as pain caused by trauma or anatomic Structural deformity (herniated nucleus pulpous). Mechanical low back pain is a primary contributor to disability. Mechanical low back pain is associated with neck and trunk musculoskeletal weakness. Objective: To determine the effectiveness of lower back strengthening exercises combined with neck and upper trunk activities in alleviating low back pain. Methodology: A total 30 subjects with mechanical low back pain were chosen using convenient sampling technique based on inclusion and exclusion criteria. Patients were split into two groups (Conventional group-15, Intervention group-15). The Conventional group received Interferential therapy (IFT) and strengthening exercise for lower back. The Intervention group received Interferential therapy (IFT) and strengthening exercise for lower back along with the neck and upper trunk exercise. For a period of four weeks, three sets of 15 repetitions were completed during each of the interventions. The Oswestry disability index was used as an outcome measure to assess how much pain and disability each participant was experiencing. Results: The mean value of pre-test was 44.87 and the post-test was 38.60 for conventional group and the mean value of pretest was 45.60 and the post test was 26.07 for intervention group. Conclusion: From the study it has been concluded that neck and upper trunk Exercises combined with conventional protocol were shown to be more successful than Conventional protocol alone in the recovery of patients with mechanical low back pain.